Terapi Kipas untuk Meredakan Sesak Napas (Journal of Telenursing (JOTING), 2021)
This study aims to provide evidence-based information to support nursing care with clinical expertise in relieving dyspnea. The method used is a literature review on the Pubmed, EBSCO Host, Google Scholar and ClinicalKey databases with predetermined keywords. The results showed that the fan therapy intervention had a beneficial effect in relieving dyspnea experienced by terminal cancer patients. In conclusion, fan therapy intervention proved to be effective in reducing dyspnea.Keywords: Dyspnea, Fan-on-Face Therapy, Terminal Cancer